Football and Geopolitics - Giuseppe SCUTTI; Jan A. WENDT (Editura Universităţii din Oradea, 2016)
The relationship between sport and politics is anything but a field on which moving easily, especially if you are not clear on what you want to focus your attention; but the football peculiarities in the process of defining its own geopolitics is widely comparable to that pure in the strict sense and even seems to be able to anticipate the latter in the process of defining the current international assets. This is because football is always one of the greatest expressions of the contact between sport, politics and reference civil society. The reflection of football in the geopolitics is a maze, it means to enter an intricate parallels system, because numerous are the points of contact and common elements between the two universes. This sport is one of the largest globally recognized phenomenon, is a huge empire: it is more widespread than democracy, the Internet and the market economy. An super ordinate institution to the standardized geopolitical system such as FIFA, has taken a leading role over the years and it has gone much further than the original powers conferred on it as a non-governmental institution. It has more members than the UN and within it there are federations such as Hong Kong, Macao and Taiwan which have preserved their status of football autonomy despite the reunification with China and therefore not recognized by the UN as a state entity. Football allows to have great visibility and legitimize concretely the own international position. This sport enters, in fact, among the new criteria by which to evaluate an international power, like demography, technological development, economy and military power. The fact that a national football team or the recognition of a football federation by FIFA is so important in the affirmation of their own identity, is a symptom that football more of other elements can personifying the "real" state.